Engineering of silicone-based mixtures for the digital light processing of Åkermanite scaffolds. Issue 7 (July 2020) - Dasan, Arish; Elsayed, Hamada; Kraxner, Jozef; Galusek, Dušan; Colombo, Paolo; Bernardo, Enrico
Abstract: Silicones mixed with oxide fillers are interesting precursors for several bioactive glass-ceramics. A key point is represented by the coupling of synthesis and shaping, since highly porous bodies, in form of foams or scaffolds, are first manufactured with silicones in the polymeric state, at low temperature, and later subjected to ceramic transformation. After successful application of direct ink writing, the present study illustrates the tuning of silicone-based mixtures in order to form åkermanite (Ca2 MgSi2 O7 ) reticulated scaffolds by digital light processing. This implied the selection of commercial silicones, producing stable and homogeneous blends with a photocurable resin and enabling the manufacturing of defect-free printed scaffolds, before and after firing, without fillers. The blends were further refined with the introduction of fillers, followed by firing at 1100 °C, in air. Optimized samples (from H44 resin) and reactive fillers (including up to 4.5 wt.% borax additive), led to crack-free and phase-pure scaffolds with microporous struts.